Implementing DevOps and SRE Practices across Industries: A Comparative Analysis - Raghavendra Rao Kanakala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the implementation and impact of DevOps and Site Reliability Engineering (SRE) practices across three distinct industries: hardware and services, financial services, and publishing. Through a comprehensive article analysis of case studies, interviews, and performance metrics, we investigate how these methodologies are adapted to meet industry-specific challenges while identifying common themes in their application. The article reveals significant improvements in deployment frequency, system reliability, and scalability across all sectors, demonstrating the transformative potential of DevOps and SRE. We also uncover key challenges, including cultural resistance and skills gaps, that organizations must overcome for successful implementation. The article provides insights into the integration of artificial intelligence, compliance measures, and content delivery optimization within DevOps frameworks. Additionally, we discuss emerging trends such as the increasing focus on edge computing and sustainability. This article offers valuable guidance for practitioners and organizations seeking to leverage DevOps and SRE practices to enhance their software delivery processes and operational efficiency in an increasingly competitive digital landscape.
Keywords: DevOps; Site Reliability Engineering (SRE); Continuous Integration/Continuous Delivery (CI/CD); Industry-specific adaptations; Automation in software delivery